1985
DOI: 10.1002/pssa.2210870227
|View full text |Cite
|
Sign up to set email alerts
|

Hole-induced exoelectron emission and luminescence of corundum doped with Mg

Abstract: Thermally stimulated exoelectron emission (TSEE) and thermally stimulated luminescence (TSL) preliminary excited by X‐rays of Al2O3 single crystals containing different amounts of Mg impurities and treated under oxiding and reducing conditions are investigated. TSEE and TSL are found to be due to the recombination process of holes thermally released from traps on Mg2+ ions (TSEE and TSL peaks at 230 K) as well as of electrons thermally released from traps (TSEE and TSL peaks at 255 K). TSEE is observed synchro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…There is also evidence for another type of defect which is originated by the removal of cations from the oxide. [55][56][57][58][59][60] Nevertheless, oxygen vacancies are thought to be the most stable defects with characteristic optical absorption spectra showing an absorption band at 6.05 eV, which was found to be formed by two peaks at 5.91 and 6.22 eV and, again as in the case of MgO, are attributed to F ϩ and F centers in ␣-Al 2 O 3 . 56 The number of electrons present at these point defects and their spatial extent affects the electronic properties of adsorbed species and consequently they may be responsible for the catalytic activity of the support.…”
Section: Introductionmentioning
confidence: 99%
“…There is also evidence for another type of defect which is originated by the removal of cations from the oxide. [55][56][57][58][59][60] Nevertheless, oxygen vacancies are thought to be the most stable defects with characteristic optical absorption spectra showing an absorption band at 6.05 eV, which was found to be formed by two peaks at 5.91 and 6.22 eV and, again as in the case of MgO, are attributed to F ϩ and F centers in ␣-Al 2 O 3 . 56 The number of electrons present at these point defects and their spatial extent affects the electronic properties of adsorbed species and consequently they may be responsible for the catalytic activity of the support.…”
Section: Introductionmentioning
confidence: 99%
“…The nature of such centers as well as their electronic structure including the F + centers (i.e. one electron trapped at oxygen vacancy), has been investigated [2][3][4]. Here it was shown that such centers can be thermally ionized and when present in sufficient concentration, can impart dosimetric utility to alumina.…”
Section: Introductionmentioning
confidence: 95%
“…It was found that the sizes of crystals in the synthesized anion defective ceramics did not exceed 150-200 nm. Furthermore, it is known that magnesium ions encourage the formation of additional centers, includ ing oxygen vacancies, in aluminum oxide [15].…”
Section: Objects Of Investigation and Experimental Techniquementioning
confidence: 99%